Juizados especiais cíveis estaduais 4.0: acesso à justiça e exclusão digital em um Brasil de desiguais: caminhos possíveis - Moraes Filho, Luís Ferreira de (2023)
Digital technology has caused countless paradigm shifts in various fields of human life. Private and public spaces have suffered significant influxes from the new way – the digital one – of interaction between people, between governments and between these and those. In this scenario, the typical state functions, also reconfigured by the technological factor, are increasingly moving away from traditional analog operational platforms towards digital spaces, seeking legitimacy for such a change in the official discourse that technology brings citizens closer to the State. Taking advantage of the same justification, associating it, in addition, with the search for greater efficiency and speed in the treatment of judicial demands, the Brazilian Judiciary has aimed at transforming justice into a digital service, in prestige to the dear fundamental right of Access to Justice, now democratized as never before in history. From this context, this research work raises reflections on the limits imposed by the chronic situation of digital exclusion in Brazil to this intended democratization of Access to Justice, especially when considering the Special Civil Courts, created to deal with simple and low-value demands moved by citizens who are economically vulnerable and, not infrequently, technically unassisted, exactly the public that, for the most diverse reasons, coincides with the profile of Brazilian men and women without connection to the world wide web of computers and/or without sufficient literacy for a self-determined role in a digital ecosystem. Based on a literature review and qualitative data analysis of the Brazilian reality, adopting a research method with a deductive and descriptive nature, the research concludes that, if on the one hand, a digital justice service builds bridges of access to justice for many people (and, for this reason, it really needs to be promoted), on the other hand, it builds walls that are difficult (or impossible) to climb for millions of women and men. Proposals to equate these antagonistic frameworks are presented at the end, highlighting the investment in public policies for digital inclusion in Brazil, especially educational ones, as well as the need for a transition plan between the analogue and digital frameworks, with support from the State to those who are unable to carry out this transition.